High prevalence of dengue, Zika, and chikungunya viruses in blood donors during a dengue outbreak and an endemic period in Colombia - Cáceres Munar, Brian Alejandro; Urbina, Adriana; Ortíz, Tatiana; Rodríguez, Ayda; Fernández, Olga Lucía; Ospina, Luisa Fernanda; Flórez, Iris; Uribe, Dora; Alvarado, Celia; Calvo, Eliana Patricia; Delgado, Félix Giovanni; Castellanos, Jaime Eduardo (Frontiers in Medicine, 2024)
Objective Arboviruses pose a challenge in ensuring the supply of pathogen-free blood components because they are not routinely screened in blood banks, and blood components from infected asymptomatic donors could be transfused. This study aimed to detect and characterize arboviral infections in Colombian blood donors. Methods In a cross-sectional study, the prevalence of dengue (DENV), Zika (ZIKV), and chikungunya (CHIKV) viruses and co-infections of blood donors were compared between an epidemic period (November 2019–February 2020, n = 462) and an endemic period (November 2021–August 2022, n = 1,119). Viral RNA from each donor serum was purified, and the viruses were detected using a previously standardized multiplex hemi-nested RT-PCR protocol. Subsequently, donors who tested positive were surveyed 15 days after the detection of the virus to identify clinical characteristics related to the arboviral infection. The prevalences of each virus were presented as percentages and compared between epidemic and endemic periods. Results Significantly higher prevalences were found in the epidemic period compared with the endemic period for DENV (14.5 vs. 1.9%), ZIKV (7.8 vs. 0.3%), CHIKV (8 vs. 3.3%), and co-infections (4.3 vs. 0.2%). The survey response rate of positive donors in the two periods was 83/175 (47%). In total, 57% of the donors surveyed were asymptomatic. Symptomatic donors most frequently reported headache (31%), malaise (13%), arthralgia (10%), and fever/chills (8%). Conclusion The prevalence observed in epidemic and endemic periods was higher than that reported in other studies in the Americas. The high proportion of asymptomatic cases found, in addition to the mild and nonspecific manifestations among the symptomatic, may limit the effectiveness of the donor selection criteria used to mitigate the risk of transfusion-transmitted arboviruses.